2018
DOI: 10.1111/jcmm.13975
|View full text |Cite
|
Sign up to set email alerts
|

Vildagliptin improves high glucose‐induced endothelial mitochondrial dysfunction via inhibiting mitochondrial fission

Abstract: The dipeptidyl peptidase 4 inhibitor vildagliptin (VLD), a widely used anti‐diabetic drug, exerts favourable effects on vascular endothelium in diabetes. We determined for the first time the improving effects of VLD on mitochondrial dysfunction in diabetic mice and human umbilical vein endothelial cells (HUVECs) cultured under hyperglycaemic conditions, and further explored the mechanism behind the anti‐diabetic activity. Mitochondrial ROS (mtROS) production was detected by fluorescent microscope and flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 43 publications
0
34
1
Order By: Relevance
“…SIRT3 is localized in mammalian mitochondria and deficiency of SIRT3 is detrimental to mitochondrial function. Mitochondrial oxidative stress leads to mtDNA damage and lower mtDNA copy number indicates serious mitochondrial dysfunction, contributing to endothelial dysfunction [ 31 , 32 ]. The results showed decreased mtDNA copy number in thoracic aorta of WT diabetic mice, which was markedly increased after DHY treatment.…”
Section: Resultsmentioning
confidence: 99%
“…SIRT3 is localized in mammalian mitochondria and deficiency of SIRT3 is detrimental to mitochondrial function. Mitochondrial oxidative stress leads to mtDNA damage and lower mtDNA copy number indicates serious mitochondrial dysfunction, contributing to endothelial dysfunction [ 31 , 32 ]. The results showed decreased mtDNA copy number in thoracic aorta of WT diabetic mice, which was markedly increased after DHY treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In the meantime, DRP1-S616 phosphorylation was decreased, while DRP1-S637 phosphorylation was increased, ultimately leading to mitochondrial fission [ 229 ]. Vildagliptin improved mitochondrial dysfunction in diabetic ECs, possibly by blunting DRP1-dependent mitochondrial fission by inducing AMPK activation [ 230 ]. Therefore, attenuation of mitochondrial fission by means of activating AMPK may represent a promising approach for macrovascular complications in diabetic patients.…”
Section: Cardio-metabolic Diseasesmentioning
confidence: 99%
“…Progression of these risk factors underlie the development of atherosclerosis and cardiovascular diseases [41]. Liu et al (2019) demonstrated that vildagliptin promotes NO (nitric oxide) production and restores physiological ROS synthesis deregulated under diabetic conditions. Vildagliptin also improves diabetes-induced mitochondrial dysfunction.…”
Section: Vascular Endotheliummentioning
confidence: 99%
“…Drp1 and Fis1 (dynamin-related proteins) are essential regulators of mitochondrial fission. Diabetic state is characterized by significantly increased expression of Drp1 and Fis1 [17]. The usage of Drp1 inhibitor mdivi¬1 (mitochondrial division inhibitor 1) () inhibits cardiomyocyte cell death after cardiac arrest.…”
Section: Vascular Endotheliummentioning
confidence: 99%
See 1 more Smart Citation